Clinico-radiological features of ileocaecal duplication cyst in children - Ab. Rahman, Norhafiza; Othman, Mohd Yusran; Abdullah, Mohd Yusof; Che Daud, Che Zubaidah (Kulliyyah of Medicine, IIUM, 2022)
Enteric duplication cyst (EDC) is a rare malformation of the alimentary tract which can potentially cause intestinal obstruction in children. It can cause obstruction directly either by narrowing the bowel lumen, or indirectly by causing an intussusception. We are reporting three cases of ileocaecal EDC in children who presented with symptoms of distal bowel obstruction; one case of ileal EDC with intussusception and two cases of chronic obstruction by an EDC at caecum and terminal ileum. Ultrasound showed a typical cystic lesion with gut signature sign in two of them. Resection was performed in all cases; primary repair was performed in the intussusception case and diversion stoma with delayed closure was performed in the other two cases with chronic obstruction.